2017
DOI: 10.22192/ijcrms.2017.03.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Portal Hypertension Doppler Parameters after Hepatitis C Virus Eradication in Patients with Definite Fibrosis

Abstract: Backgrounds and aims: Eradication of hepatitis C virus (HCV) infection with direct-acting antivirals (DAAs)nowadays is almost always successful and sustained virological response (SVR) occurs in more than 90% of cases and this prevent more fibrosis and preclude the progression of portal hypertension (PH). We aimed to evaluate the portal hypertensive Doppler parameters as a marker of PH after treatment of HCV with DAAs. Methods: 200 patients with post chronic HCV infection and definite liver fibrosis ≥F2 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Regarding portal vein velocity, our results are in line with Soliman et al [ 25 ], where PVV improved significantly from 11.889 ± 3.529 cm/s to 15.094 ± 4.250 cm/s, with ( p -value ≤ 0.001*), as well as Mahmoud et al [ 26 ], where PVV was increased significantly from 13.61 ± 2.53 cm/s at baseline to 14.72±2.67 cm/s at EOT and to 15.81±2.067 cm/s at SVR 48, with p -value ≤ 0.001*.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding portal vein velocity, our results are in line with Soliman et al [ 25 ], where PVV improved significantly from 11.889 ± 3.529 cm/s to 15.094 ± 4.250 cm/s, with ( p -value ≤ 0.001*), as well as Mahmoud et al [ 26 ], where PVV was increased significantly from 13.61 ± 2.53 cm/s at baseline to 14.72±2.67 cm/s at EOT and to 15.81±2.067 cm/s at SVR 48, with p -value ≤ 0.001*.…”
Section: Discussionsupporting
confidence: 92%
“…In our results, portal vein diameter showed 82.50% sensitivity and 95% specificity at cutoff value (> 13.8 mm), to predict the presence of CSPH in HCV-related liver cirrhosis, while showed 50% sensitivity and 100% specificity, at cutoff value (≤ 14 mm), to predict reversibility of CSPH. These findings are similar to Hagen-Ansert [ 27 ], who reported that a diameter (> 13 mm) was considered as a predictor of PH in patients with cirrhosis, but unlike Mahmoud et al [ 26 ] and Mihai et al [ 28 ], as their results were insignificant regarding PVD.…”
Section: Discussionsupporting
confidence: 87%